Periodic Boehmians - Dennis Nemzer (International Journal of Mathematics and Mathematical Sciences)
A class of generalized functions, called periodic Boehmians, on the unit circle, is studied. It is shown that the class of Boehmians contain all Beurling distributions. An example of a hyperfunctlon that is not a Boehmian is given. Some growth conditions on the Fourier coefficients of a Boehmian are given. It is shown that the Boehmians, with a given complete metric topological vector space topology, is not locally bounded.